The Importance of Context, Reflection, Interaction, and Consequence in Rural Music Education Practice - Anita Prest (Journal of Research in Rural Education, 2013)
In this paper, I argue that aesthetic music education philosophy, which undergirds many current music teacher education programs, textbooks, practices, and networks, fosters assumptions that are not applicable to rural settings. I outline and critique the main principles of this philosophy and demonstrate the ways in which music teachers' habits and assumptions, informed by aesthetic music education philosophy, might change due to doubts and reflection incurred by experiencing the structural and dynamic realities unique to rural music education practice. My viewpoint is derived from my personal experiences, conversations, and observations as a music educator in rural British Columbia over a sixteen-year period. I explore the themes common to Aristotle's conception of praxis, pragmatist philosophy, and praxial music education philosophy that might better inform British Columbian rural music teachers' practice and inquiry, and teacher education programs. I specify the ways in which rural music educators, by adopting a praxialist orientation, might consciously interact, deliberate, and make imposed structural and attitudinal boundaries more porous and less potent (Doll, 2006), thereby setting the stage for the ongoing transformation of their educational practice to better suit their rural context. Finally, I suggest that music teacher education curricula adopt a praxial music education orientation that will assist music teacher candidates to comprehend the notion of "enabling constraints," the importance of developing relationships and networks, and the vital role of community in rural education.